How about running on Mars? Influence of sensorimotor coherence on running and spatial perception in simulated reduced gravity - Keime, Marie; Chomienne, Loïc; Goulon, Cédric; Sainton, Patrick; Lapole, Thomas; Casanova, Rémy; Bossard, Martin; Nicol, Caroline; Martha, Cécile; Bolmont, Benoit; Hays, Arnaud; Vercruyssen, Fabrice; et al. (Frontiers in Physiology, 2023)
Motor control, including locomotion, strongly depends on the gravitational field. Recent developments such as lower-body positive pressure treadmills (LBPPT) have enabled studies on Earth about the effects of reduced body weight (BW) on walking and running, up to 60% BW. The present experiment was set up to further investigate adaptations to a more naturalistic simulated hypogravity, mimicking a Martian environment with additional visual information during running sessions on LBPPT. Twenty-nine participants performed three sessions of four successive five-min runs at preferred speed, alternating Earth- or simulated Mars-like gravity (100 vs 38% BW). They were displayed visual scenes using a virtual reality headset to assess the effects of coherent visual flow while running. Running performance was characterized by normal ground reaction force and pelvic accelerations. The perceived upright and vection (visually-induced self-motion sensation) in dynamic visual environments were also investigated at the end of the different sessions. We found that BW reduction induced biomechanical adaptations independently of the visual context. Active peak force and stance time decreased, while flight time increased. Strong inter-individual differences in braking and push-off times appeared at 38% BW, which were not systematically observed in our previous studies at 80% and 60% BW. Additionally, the importance given to dynamic visual cues in the perceived upright diminished at 38% BW, suggesting an increased reliance on the egocentric body axis as a reference for verticality when the visual context is fully coherent with the previous locomotor activity. Also, while vection was found to decrease in case of a coherent visuomotor coupling at 100% BW (i.e., post-exposure influence), it remained unaffected by the visual context at 38% BW. Overall, our findings suggested that locomotor and perceptual adaptations were not similarly impacted, depending on the -simulated- gravity condition and visual context.